Gambaran Self-Efficacy Lansia Penderita Alzheimer yang Mengikuti Terapi Fisik, Terapi Virtual Reality dan yang Tidak Mengikuti Terapi - Brahmanda Pandya Dhipta; Evanytha; Maharani Ardi Putri (Fakultas Psikologi Universitas Pancasila, 2012)
The degeneration of functional organ is the common elderly problem. It includes cognitive and physical impairment. Besides the natural process as one of the causes, the researcher finds that this degeneration can be accelerated by the behavior of the older people in avoiding the daily activities, many of them do not feel confident to do such activities. The degeneration of functional organ is a natural process, but it can be perverted. One of the efforts to regenerate physical and cognitive function can be implemented through therapy, both physical therapy and virtual reality therapy. The both therapy closely relates to one of the sources self-efficacies; physiological state, it plays the role in health function and physical activities that requires both strength and stamina. In judging the physical ability, one can be affected by the information about his/her physical condition to face certain situation by examining his/her physiology. The older alzheimer patients are divided into three categories; those who receive physical therapy, those who receive virtual reality therapy and the rest who do not receive therapy. This research is conducted in one of the elderly home cares, which there are some older alzheimer patients who have received two programs of these therapies. The researcher is using qualitative study case method through observation and interview. The research shows that the subjects in the research have vary comprehension in seeing the abstract dimensions and self-efficacy sources.